Zinc Oxide Phytonanoparticles' Effects on Yield and Mineral Contents in Fruits of Tomato (Solanum lycopersicum L. cv. Cherry) under Field Conditions. (11th June 2021) - Gutiérrez-Miceli, Federico Antonio; Oliva-Llaven, María Ángela; Luján-Hidalgo, María Celina; Velázquez-Gamboa, María Concepción; González-Mendoza, Daniel; Sánchez-Roque, Yazmin
Abstract : The use of phytonanoparticles in agriculture could decrease the use of fertilizers and therefore decrease soil contamination, due to their size being better assimilated in plants. It is important to mention that the nanofertilizer is slow-releasing and improves plant physiological properties and various nutritional parameters. The influence of soil and foliar applications of phytonanoparticles of ZnO with the Moringa oleifera extract under three concentrations (25, 50, and 100 ppm) was evaluated on the cherry tomato crop ( Solanum lycopersicum L.). Synthesis of the phytonanoparticles was analyzed with ultraviolet-visible spectroscopy (UV-Vis) and infrared transmission spectroscopy with Fourier transform (FT-IR), as well as the analysis with the dynamic light scattering (DLS) technique. The morphometric parameters were evaluated before and after the application of the nanoparticles. The minerals' content of fruits was done 95 days after planting. Results showed that soil application was better at a concentration of 25 ppm of phytonanoparticles since it allowed the greatest number of flowers and fruits on the plant; however, it was demonstrated that when performing a foliar application, the fruit showed the highest concentrations for the elements Mg, Ca, and Na at concentrations of 511, 4589, and 223 mg kg −1, respectively.